United States and German Military Cemeteries in Italy – Cultural Perspectives - Urmson, Birgit (RIHA Journal, 2017)
The US and German military cemeteries in Italy differ greatly from one another in style and message. Art-historical methods such as stylistic analysis and iconographic interpretation along with historical research are used to explore the ideological character of each nation’s cemeteries. These, in turn, are used to illuminate aspects of the respective cultures at the time of their design and construction. The results reveal post World War II US society becoming more conformist and politically conservative and German society undergoing a redefinition of its values.